Graft Copolymerization of Methyl Methacrylate Monomer onto Starch and Natural Rubber Latex Initiated by Gamma Irradiation - S. Iskandar (Atom Indonesia, 2011)
To obtain the degradable plastic, the graft copolymerization of methyl methacrylate onto starch and natural rubber latex was conducted by a simultaneous irradiation technique. Gamma-ray from cobalt-60 source was used as the initiator. The grafted copolymer of starch-polymethyl methacrylate and the grafted copolymer of natural rubber-polymethyl methacrylate were mixed in the blender, and dried it in the oven. The dried grafted copolymer mixture was then molded using hydraulic press machine. The effect of irradiation dose, composition of the grafted copolymer mixture, film forming condition and recycle effect was evaluated. The parameters observed were tensile strength, gel fraction and soil burial degradability of grafted copolymer mixture. It was found that the tensile strength of grafted copolymer mixture increased by γ-ray irradiation. Increasing of the grafted copolymer of natural rubber-polymethyl methacrylate content, the gel fraction and tensile strength of the grafted copolymer mixture increased. The tensile strength of the grafted copolymer mixture was increased from 18 MPa to 23 MPa after recycled (film forming reprocessed) 3 times. The grafted copolymer mixture was degraded completely after soil buried for 6 months. Received: 20 July 2010; Revised: 04 February 2011; Accepted: 10 March 2011